Suitable management options to improve the productivity of rice cultivars under salinity stress - Mel, V.C.; Bado, V.B.; Ndiaye, S.; Djaman, K.; Nati, D.A.B.; Manneh, B.; Futakuchi, K. (Informa UK Limited, 2019)
Growing rice in saline soils by minimizing damage on growth and yield remains a challenge. We conducted field experiments in the Africa Rice research field located in the Senegal River delta (16° 11ʹ N, 16° 15ʹ W) to study the effects of three management options of fertilization e.g. (i) nitrogen, phosphorus, and potassium fertilization: NPK; (ii) NPK combined with zinc: NPK-Zn, and (iii) NPK combined with gypsum: NPK-gypsum on the soil salinity level, the nutrient uptake and the productivity of different rice cultivars. The whole objective of this study is to determine how zinc or gypsum associated to NPK fertilizer can improve the growth and productivity of rice crop in saline soil. Results showed that the initial soil salinity level was reduced rapidly in plots treated with gypsum. The leaf-K/Na ratio, agronomic nitrogen use efficiency (ANUE), and grain yield of rice cultivars under the salinity stress were improved by the NPK-gypsum and NPK-Zn options relatively to the NPK option, suggesting that NPK-gypsum and NPK-Zn are suitable management options in reducing adverse effect of low K/Na, low ANUE as well as to improve rice yield under salinity stress.